Femoroacetabular impingement syndrome – a pain in the hip. Issue 3 (May 2017) - Dick, Alastair; Bankes, Marcus
Abstract : The presentation of elderly patients with hip pain due to osteoarthritis is familiar to most general practitioners. Hip pain in the younger adult, particularly men, can be a less familiar and more challenging presentation. In this article the authors describe femoroacetabular impingement syndrome, an increasingly recognised cause of hip pain in the younger population.